AN ANALYTICAL STUDY OF THE SEA WATER SLIME WITH REFERENCE TO BACTERIAL FLORA. - PILLAI, A. G GOPALAKRISHNA (Fishery Technology, 2017)
A detailed study of the primary film of slime with reference to the bacterial flora, its quality and quantity, as observed on different material surfaces exposed to sea water is carried out. A correlation has been established between bacteria and slime deposited on different surfaces.